CNF-grafted carbon fibers as a binder-free cathode for LithiumOxygen batteries with a superior performance. (11th January 2018) - Zhu, Xingbao; Wu, Yuanguo; Wan, Weihua; Yan, Yingzhang; Wang, Yu; He, Xianglei; Lü, Zhe
Abstract: In this work, we report the significant enhancement of the electrochemical performance and flexibility of a lithium–oxygen battery by introducing a free-standing, binder-free carbon nano-fibers (CNF) grafted carbon paper cathode with a bimodal pore architecture. The small pore structures (∼100 nm) accommodated Li2 O2, and the large pore structures (∼10 μm) enabled effective oxygen diffusion without clogging the pores. This kind of cathode overcame some troubles of the cathode prepared by spraying coating method, such as the low utilization of substrate surface, the unreasonable aperture structure and the aggregation of active carbon material. As a result, this electrode structure imparted stability to active sites during the recovery of discharge products to the initial state, providing long-term cyclability of more than 800 cycles in a 1 M LiTFSI/TEGDME electrolyte system. In addition, the battery output a discharge capacity as high as 20000 mAh g −1 at 468 mA g −1 and exhibited a charge/discharge rate as high as 1136 mA g −1 (0.57 mA cm −2 ). The test results suggest that these CNF-grafted carbon papers have the potential to be used for oxygen/air electrodes for next-generation lithium-oxygen batteries, though the present results need to be improved to achieve performance of practical significance, namely with regard to (i) cathode mass loading to get higher areal capacity, and (ii) cycling performance at higher current density. Highlights: CNF-grafted carbon paper was prepared and used as the battery cathode. A bimodal pore architecture was presented in the battery cathode. The battery exhibits the maximum discharge capacity of 20000 mAh g −1 . The battery exhibits the maximum current density of 1136 mA g −1 (0.57 mA cm −2 ).